Mitigating operational risks and enhancing machine performance through total productive maintenance and OEE: a case study on packaging equipment - Ruspendi, Ruspendi; Rusmalah, Rusmalah; Hendra, Franka; Effendi, Riki (Jurnal Polimesin, 2025)
This study evaluates the effectiveness of a laser marking machine in an instant noodle packaging line using a Total Productive Maintenance (TPM) framework and Overall Equipment Effectiveness (OEE) metrics over a 12‑month period. A mixed‑method design combined direct observation, semi‑structured interviews with operators and technicians, and a literature review to assess availability, performance efficiency, and quality rate. The machine achieved excellent availability, averaging 98.95%, reflecting the impact of preventive maintenance in reducing unplanned downtime. Performance efficiency varied substantially, ranging from 59.13% to 93.27%, indicating significant headroom for productivity improvement through cycle‑time stabilization and minor‑stoppage reduction. The quality rate averaged 89.21% and remained relatively stable, though still short of ideal benchmarks, suggesting the need for tighter in‑process quality control. The monthly OEE peaked at 84.77% in April, approaching the JIPM benchmark of 85%, while the period average was 60.38%, underscoring the need for sustained improvement initiatives. Among the three components, performance efficiency exerted the greatest influence on OEE due to its high variability across months.